Preliminary study of Collaborative Knowledge Management System Strategic Planning (CKMS2P) Model - Hashim, Siti Noorasmah; Abdullah, Rusli; Ibrahim, Hamidah (Medwell Publications, 2017)
This study proposes a comprehensive Collaborative Knowledge Management System Strategic Planning (CKMS2P) Model to assist the Knowledge Management System (KMS) developers and implementers in managing and executing the development and implementation of CKMS systematically and strategically in the organization. The model was developed based on Systematic Literature Review (SLR) and preliminary survey was done to gauge the perception of the proposed model to support the objective of this research. The data were analyzed using the Rasch Measurement Model. The results show that the CKMS2P may assist the CKMS developers and implementers as a guideline to develop and implement CKMS in their organization comprehensively and strategically.